2022
DOI: 10.3390/ma15031250
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Adhesive Layer Thickness on the Behavior of Reinforcing Thin-Walled Sigma-Type Steel Beams with CFRP Tapes

Abstract: This paper presents selected issues related to the reinforcement of steel element cold-formed with CFRP tapes. The first section of the paper is a review of source literature and a presentation of the basic information on cold-formed thin-walled steel elements and CFRP composite materials, stressing the advantages and disadvantages of using them to reinforce steel structures. Next, the authors present original research on reinforcing bent thin-walled sigma-type steel beams using adhesive CFRP tapes. Reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…In turn, the change in the adhesive layer thickness had a negligible impact on the change in the level of deflections of the beam and strain in the tension beam flange. Performed numerical analyses also confirmed the influence of the thickness of the glued joint layer on the moment of failure of the joint, which was also demonstrated in numerical analyses for a different beam cross-section described in [ 13 ]. For the beams analyzed in this study, numerical analyses showed that the increase in the thickness of the adhesive layer significantly affected the decrease in the load value at which the tape detached; the difference in the load values obtained for the extreme adhesive layer thickness was 9.76 kN.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In turn, the change in the adhesive layer thickness had a negligible impact on the change in the level of deflections of the beam and strain in the tension beam flange. Performed numerical analyses also confirmed the influence of the thickness of the glued joint layer on the moment of failure of the joint, which was also demonstrated in numerical analyses for a different beam cross-section described in [ 13 ]. For the beams analyzed in this study, numerical analyses showed that the increase in the thickness of the adhesive layer significantly affected the decrease in the load value at which the tape detached; the difference in the load values obtained for the extreme adhesive layer thickness was 9.76 kN.…”
Section: Discussionsupporting
confidence: 67%
“…The material parameters for the main test object, which was a steel beam with a rectangular cross-section, were described by an elastic–plastic material model, the data of which were presented in the test subject description stage. The adhesive layer and the composite tape had data adequate in comparison to the information presented in a thematically similar scientific publication [ 13 ]. Material data for the composite tape and adhesive were taken mainly from [ 14 ].…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…This is a major limitation for scientists who research this type of structure. It should be added that FEM modelling may be interesting for considering the progressive failure and failure processes in composites [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. For this reason, future research directions will focus on the analysis of the post-critical state in the full range of loads leading to the damage and failure of the composite structure.…”
Section: Resultsmentioning
confidence: 99%
“…The sheets are cold-bended to obtain the desired cross-section; therefore, due to production methods, there are obvious limitations on the shape of thin-walled cross-sections. The most popular in structural engineering are Z or C profiles [ 4 , 5 ]; however, Sigma profiles [ 6 , 7 ] have also recently been used. Structural members with thin-walled cross-sections are used in light structures as one of the first load-bearing elements; for instance in roof purlins, but also as secondary load-bearing elements in steel sheds, or supporting structures in photovoltaic installations, such as rafters or columns.…”
Section: Introductionmentioning
confidence: 99%